Surgical management of gall bladder perforation as a complication of cholelithiasis: A case series - Shailendra Kaushik; Puneet Jain; Mehar Kashyap; Ashok Kumar (Asian Journal of Medical Sciences, 2025)
Gallbladder perforation is a less common clinical disease due to its rarity and diagnostic challenge. It is a rare but potentially fatal adverse consequence of acute cholecystitis. A single institution’s experience with managing this condition is incorporated into this case series.